Rumen protozoa - Abdullah, Norhani; Ho, Y. M. (1990)
Rumen protozoa have been shown to invade and ingest plant particles (Bauchop, 1979) and to produce the enzymes required for the digestion of complex proteins and carboyhdrate. (Coleman, 1985). This paper reports a morphological study on rumen protozoa preset in the rumen liquor of cattle and swamp buffaloes fed fibrous diets. Investigations on the different morpholoqical forms of rumen liquor protozoa were carried out using samples collected from 4 Kedah-Kelantan cattle (Bos indicus) and 4 swamp buffaloes (Bubalus bubalis) at slaughter before the morning feed. Two cattle and 2 buffaloes had been grazing Setaria aphacelata var. splendida pasture for 5 weeks, while another 2 cattle and 2 buffaloes had been stall fed with palm press fibre (PPF)-based diet for 3 weeks. The PPF-based diet consisted of a mixture of PPF and 10 percent molasses (1:1) fed ad libitum., 400 g fish meal, 40 g urea and 6 g (NH4)2S04. Rumen liquor was strained through 4 layers of muslin cloth, fixed and stained for protozoa to be observed under the light microscope. Rumen liquor was also sampled from fistulated animals for protozoal study. A sampling probe covered with two layers of nylon stockings was inserted into the ventral rumen and the rumen liquor collected in the probe was withdrawn with a syringe. Sampling was done before feeding, and at 1, 3 and 6 h after the onset of feeding. Rumen liquor collected was immediately fixed and stained for protozoa. The liquor was observed for the types of ciliates present and their counts at the various sampling times.